2016
DOI: 10.1111/ivb.12112
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in the Mediterranean endemic gorgonian Spinimuricea klavereni (Anthozoa, Octocorallia, Plexauridae)

Abstract: Spinimuricea klavereni is a Mediterranean endemic gorgonian that is rarely encountered, probably because it typically occurs at depths below 50 m. It is exceptionally common in the northern Marmara Sea, with an unusually shallow upper depth limit of ~20 m. The reproductive biology of this species was studied during a one year period off Büyükada, in the northeastern Marmara Sea. Spinimuricea klavereni is a gonochoric broadcast spawner with an almost even sex ratio. Colonies were ~15 cm in height at first repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This rare gorgonian species typically inhabits depths below recreational diving (Table 1) and this could be one of the reasons for the lack of knowledge on its distribution and biology in general (TOPÇU & OZTÜRK, 2013, 2016a. Exceptionally shallow and dense populations of Spinimuricea klavereni in Marmara Sea gave the opportunity for the first studies on the growth rate and reproduction of this species (TOPÇU & OZTÜRK, 2016a, 2016b. Furthermore, it seems that this dense population could be a result of the specific oceanographic conditions of the Marmara Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rare gorgonian species typically inhabits depths below recreational diving (Table 1) and this could be one of the reasons for the lack of knowledge on its distribution and biology in general (TOPÇU & OZTÜRK, 2013, 2016a. Exceptionally shallow and dense populations of Spinimuricea klavereni in Marmara Sea gave the opportunity for the first studies on the growth rate and reproduction of this species (TOPÇU & OZTÜRK, 2016a, 2016b. Furthermore, it seems that this dense population could be a result of the specific oceanographic conditions of the Marmara Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in the Marmara Sea by TOPÇU and OZTÜRK (2016a, 2016b) reported the highest density of S. klavereni (3.1 ind. m -2 ) and highlighted depth range, morphometry, growth rates and reproduction (TOPÇU & OZTÜRK, 2016a, 2016b. Being these the only in-depth studies on the species, it is not strange that OTERO et al, (2017) in the Overview of the conservation status of the Mediterranean Anthozoa classified S. klavereni as Data Deficient.…”
Section: Introductionmentioning
confidence: 99%
“…Four gorgonians encountered in the region all have different life history traits and their recovery patterns might proceed distinctly in space and time. Spinimuricea klavereni , for example, grows relatively fast and has a high reproductive output throughout the year in the Sea of Marmara (Topçu & Öztürk, 2016 a , 2016 b ). The confamilial gorgonian P. clavata is, on the other hand, a long-lived, slow-growing species, with high reproductive output but low recruitment (Coma et al ., 1995; Linares et al ., 2008 b ).…”
Section: Discussionmentioning
confidence: 99%
“…These octocorals, of course, might provide limited insight into the scleractinian stress response; however, octocorals are a significant component of cnidarian diversity in their own right (McFadden et al. , ; Coelho & Lasker ; Topçu & Öztürk ).…”
mentioning
confidence: 99%